Analysis and Evaluation of the Quality of the Services Provided by BSR „Passengers“ LTD (UNWE Yearbook, 2024)
Railway transport allows people to enjoy the freedom to travel, while simultaneously creating economic growth and jobs. Its technological development is of key importance for any modern society, as it helps the achievement of social and regional cohesion. At the same time, it needs to be sustainable, considering the increased amount of resources that goes into carrying out freights and ecological restrictions. The supply of high-quality transport services in synergy with modern infrastructure is vital for highlighting the economic strengths of each individual region in the country, as well as facilitating economic and social cohesion. Effective transport services influence the competitiveness of commerce, accessibility and prices. The quality of the services provided by BSR has a strong reflection on production processes and the selection of trading partners. The purpose of the study is to analyze the primary indicators that influence the quality of the transport services that BSR provides. The factors that determine the behavior of transport service consumers when they choose their mode of transportation have been analyzed. The quality of freights carried out by the national railway carrier has been evaluated. At the end of the study the achieved results are outlined and specific recommendations pertaining to the development of railway transport in Bulgaria are made.